Molecular Characterization and the Antimicrobial Resistance Profile of Salmonella spp. Isolated from Ready-to-Eat Foods in Ouagadougou, Burkina Faso - Soubeiga, Adama Patrice; Kpoda, Dissinviel Stéphane; Compaoré, Muller K. A.; Somda-Belemlougri, Asseto; Kaseko, Ndamiwe; Rouamba, Sibiri Sylvain; Ouedraogo, Sandrine; Traoré, Roukiatou; Karfo, Paulette; Nezien, Désiré; Nikiéma, Fulbert; Kabre, Elie; et al. (International Journal of Microbiology, 2022)
The emergence of antimicrobial-resistantfood-borne bacteria is a great challenge to public health. This study was conducted to characterize and determine the resistance profile of Salmonella strains isolated from foods including sesames, ready-to-eat (RTE) salads, mango juices, and lettuce in Burkina Faso. One hundred and forty-eight biochemically identified Salmonella isolates were characterized by molecular amplification of Salmonella marker invA and spiC, misL, orfL, and pipD virulence genes. After that, all confirmed strains were examined for susceptibility to sixteen antimicrobials, and PCR amplifications were used to identify the following resistance genes: blaTEM, temA, temB, StrA, aadA, sul1, sul2, tet(A), and tet(B). One hundred and eight isolates were genetically confirmed as Salmonella spp. Virulence genes were observed in 57.4%, 55.6%, 49.1%, and 38% isolates for pipD, SpiC, misL, and orfL, respectively. Isolates have shown moderate resistance to gentamycin (26.8%), ampicillin (22.2%), cefoxitin (19.4%), and nalidixic acid (18.5%). All isolates were sensitive to six antibiotics, including cefotaxime, ceftazidime, aztreonam, imipenem, meropenem, and ciprofloxacin. Among the 66 isolates resistant to at least one antibiotic, 11 (16.7%) were multidrug resistant. The Multiple Antimicrobial Resistance (MAR) index of Salmonella serovars ranged from 0.06 to 0.53. PCR detected 7 resistance genes (tet(A), tet(B), blaTEM, temB, sul1, sul2, and aadA) in drug-resistant isolates. These findings raise serious concerns because ready-to-eat food in Burkina Faso could serve as a reservoir for spreading antimicrobial resistance genes worldwide.